The first pagurapseudid species (Peracarida: Tanaidacea) from New Zealand with remarks on paguridean (Decapoda: Paguridea) and pagurapseudid convergence and competition - Bird, Graham J.; Webber, W. Richard (Zootaxa, 2015)
A new species of pagurapseudid, Macrolabrum maui, is described from the lower eulittoral rocky shore on the East Coast of the North Island, New Zealand. It is similar to M. haikung from Bass Strait, Australia and M. distonyx from New Caledonia. Males and females show little dimorphism. Typical of the subfamily Pagurapseudinae, M. maui inhabits shells of micro-molluscs such as the gastropods Eatoniella, Merelina, and Pisinna. A dichotomous key to the species of Macrolabrum is given. Possible competition for micro-mollusc shells between small pagurideans, notably their glaucothoe stage, and pagurapseudids is considered based on their convergent morphologies and on body sizes.